2020
DOI: 10.1002/adtp.202000116
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid Conjugates of Vorinostat and Bexarotene for Treatment of Cutaneous Malignancies

Abstract: Skin cancer is the most common class of malignancies in humans with increasing incidence worldwide. Although surgery remains the most common treatment approach, relapses after surgery necessitate other treatment options. There is an increasing clinical demand for topical treatments for skin cancer that can improve the drug's cutaneous localization while limiting systemic absorption. In this study, hyaluronic acid (HA) conjugates are successfully synthesized by attaching a third-generation retinoid (bexarotene)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…HCl and potassium salt of Oxyma forming the corresponding active ester ( Cherkupally et al, 2013 ; Jad et al, 2015 ), which was allowed to react with the free amino groups of Lf to create an amide bond ( Scheme 1 ). MTX–Lf conjugate could minimize the side effects, augmenting MTX accumulation within cancer cells and thus maximize its anti-tumor efficacy ( Anwar et al, 2018 ; Sallam et al, 2020 ). Stehle et al previously reported the synthesis of the MTX–HSA conjugate by direct carbodiimide coupling of MTX to the lysine residue in albumin ( Stehle et al, 1997 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HCl and potassium salt of Oxyma forming the corresponding active ester ( Cherkupally et al, 2013 ; Jad et al, 2015 ), which was allowed to react with the free amino groups of Lf to create an amide bond ( Scheme 1 ). MTX–Lf conjugate could minimize the side effects, augmenting MTX accumulation within cancer cells and thus maximize its anti-tumor efficacy ( Anwar et al, 2018 ; Sallam et al, 2020 ). Stehle et al previously reported the synthesis of the MTX–HSA conjugate by direct carbodiimide coupling of MTX to the lysine residue in albumin ( Stehle et al, 1997 ).…”
Section: Resultsmentioning
confidence: 99%
“…The latter have been employed as a strategy to enhance drug stability, solubility, and circulation time ( Tran and Tran, 2019 ). Moreover, they help protect the normal body cells against the cytotoxic effect of chemotherapeutics by controlling the drug to be released at specific sites and in the presence of specific enzymes ( Dolz-Pérez et al, 2020 ; Sallam et al, 2020 ). Additionally, Lf being a component of body innate immune system possesses merits compared to synthetic polymers that are employed for the synthesis of polymer–drug conjugates.…”
Section: Introductionmentioning
confidence: 99%
“…Tailored MD-α-TOC bioconjugates were synthesized following a simple carbodiimide method. 12 , 26 Chemical entities and physicochemical properties of maltodextrin-α-tocopherol were investigated and confirmed by several techniques. 12 Noteworthy, synthesized biopolymers were obtained by utilizing two natural substrates whose merits were numerous owing to their biocompatibility, low immunogenicity, well-known structure and good tolerability within the human body.…”
Section: Resultsmentioning
confidence: 99%
“… 61 HA has been widely implemented as a delivery agent of microscale particles for intranasal delivery of influenza vaccines. 62 It also acts as a transdermal nanocarrier of macromolecules, such as human growth hormone 63 as well as small molecules 64 and peptides.…”
Section: Noninvasive Transcutaneous Immunizationmentioning
confidence: 99%